Business games in administration (2015)
This research report presents an exploration and description of the business games Anno and Carnival tycoon, in which, there is an analysis of the presence of the administration areas such as Human Resources, Marketing, Management and Finance in each game, taking into account the qualitative paradigm that was carried out through the "coding frames" instrument.